Anthro-Historiographic Notes on the Indegenous People of Negros Oriental - Mascuñana, Rolando V. (Silliman Journal, 2023)
OF THE RECOGNIZED Indigenous Peoples or Indigenous Cultural Communities (IPs/ICCs) in the Philippines today, two groups live in the hinterlands of the province of Negros Oriental. These are the Negritos, locally known as Ata, of Barangay Canggohob, Mabinay and the Bukidnon (literally, hill/mountain people) of Barangay Tayawan, Bayawan and Barangay Cabatuanan, Basay in southern Negros.